Evaluasi Platform Perangkat Keras Sistem Tertanam untuk Unit Kontrol Parkir Otomatis - Wahyu Dewanto; Agung Fathurrahman; Agus Bejo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Automatic parking system is one of the parking management technologies that is widely used in various institutions today. An automatic parking system works by controlling a parking gate automatically to open and close the gate and record the vehicle’s license plate when entering and exiting using access control such as a smart card or radio frequency identification (RFID). One of the challenges in implementing an automatic parking system is traffic congestion during high traffic conditions. This challenge arises because the control unit in the automatic parking system takes a relatively long time to process and store images from the camera. This research examined several embedded system platforms as automatic parking system control units, including Raspberry Pi 3B, Raspberry Pi 4B, and Orange Pi Zero Plus. The evaluation is intended to find the best control unit platform based on several criteria, such as the execution time in capturing images, storing images, and the consumed power. From the evaluation results, it can be concluded that the Raspberry Pi 4B platform results in the fastest execution time for capturing and storing images, with an average time of 1,827.9 ms. Meanwhile, the Orange Pi Zero Plus platform achieves the lowest power consumption at 1.9 W. Based on the evaluation results, the Raspberry Pi 4B is recommended as the control unit if the automatic parking system requires a high-performance device. Otherwise, the Orange Pi Zero Plus is more recommended if the automatic parking system requires a low-power device.